A variational approach of stationary Boltzmann equation under a condition of Poisson type. - Almanza Caro, Mario Enrique; Andrade, Rafael Galeano (Rev. Téc. Fac. Ing. Univ. Zulia)
A functional is defined on a subset of L2 (), with bounded and so that the divergence theorem is valid. It shows that this functional is differentiable, coercive and weakly lower semi-continuous bound, and therefore has critical points which coincide with the solutions of the stationary Boltmann equation solutions under a condition of Poisson.